Analisis Pengujian Sistem RAKOON POS Berdasarkan Teori Kualitas McCall - Hastian Bayu; Adam Hendra Brata; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Software testing is a critical element of software quality assurance and represents a principal review of specifications, design and coding. Point of Sale can be interpreted as a cashier (check-out counter) with the cash register. Software Testing has many methods in testing application products, one of which is the McCall Quality Theory, this theory focuses on 3 main things namely Product Revision, Product Transisiton and Product Operation. Testing the Point of Sale system using McCall is able to help testers review and redefine the functionalities that exist in the software, the McCall method is considered to provide a more practical method in clarifying software requirements into software quality factors. Rakoon POS is a software application product made by PT. JakaMedia, based on cashier financial management, to help the financial system at the cashier, manage, and process data that is sensitive to transactions in website-based business entities. In fact, the Rakoon POS application has never been tested before using the Software Testing method, the Quality and Reliability of this product has not been proven argumentatively. With this definition outlined, McCall's quality theory is expected to be able to help improve the factors in the application of the Rakoon POS cashier system.